PENERAPAN MODEL GNT GUIDE NOTE TAKING (GNT) DALAM MENINGKATKAN HASIL BELAJAR PENDIDIKAN KEWAGANEGARAAN DI MIN TALANG EMPAT KABUPATEN BENGKULU TENGAH - Desy Aprianti (Al-Bahtsu : Jurnal Penelitian Pendidikan Islam, 2017)
Abstract: The results of this study concluded that after the teacher using the model application of the GNT, the learning outcomes of students of class V MIN Talang Four Central Bengkulu Regency, increased well, it can be seen from the test prior knowledge, the first cycle, the second cycle, with the average value of the test capability initial = 54.66, cycle I = 59.5, the second cycle = 78, while the percentage ketuntasannya initial capability test is = 30%, the first cycle that = 43.33%, the second cycle = 90%. Thus GNT models can improve student learning achievement SKI discussion events recognize the end of life of the Prophet, the students MIN Talang Four Central Bengkulu district, this is because students are directly involved in learning activities. During this time students only listen but with a model GNT students can more quickly understand what is described by the teacher. And the things that they consider the abstract into the concrete with their method of GNT.